Alinhamento entre gestão do conhecimento e estratégia competitiva: um estudo de caso numa empresa de telecomunicações - Vilaça, Débora Barbosa Guedes de Oliveira (2011)
Organizations nowadays are faced increasingly with a highly competitive environment, globalization, where the process of constant innovation has charged them a proactive and dynamic behavior, in that they often find themselves forced to anticipate the needs and desires of their customers and many cases establishing and maintaining these in same needs and desires. It is within this context that the knowledge management practices have attracted the attention of several scholars and researchers, since they allow the transformation of individual knowledge into organizational knowledge, as well as possible to generate, codify and transfer knowledge, making it the sustainable competitive advantage. Adding to that, have also studies about the competitive strategy emphasizing the need that organizations have to define a strategic behavior to suit your profile and consistent with its competitive environment. On this basis, this study brings with it the intention to show how competitive strategy and knowledge management can be aligned, especially with regard to the reality of companies in the telecommunications segment. To this end, its the main objective is to identify the alignment between knowledge management and strategy in a competitive telecommunications company. To achieve this goal, we used two theoretical models, one to investigate the practices of knowledge management and its relationship to competitive strategy, and another model to identify the competitive strategy of differentiation adopted by the organization. The use of both models enabled the creation of a closed questionnaire containing 29 questions was applied to a sample of 205 professionals, out of 253. The results show that the organization researched work based on the enabling conditions of knowledge, with emphasis on the first condition enabling that vision is to instill knowledge. In addition, we found that the company researched work based on two types of strategies, the strategy of differentiation by price and advertising. To check the alignment between the company's strategic profile linked to the way it manages its knowledge, we used the marginal homogeneity test that is suitable for multinomial and sorted into categories. By using this test, we determined that the company studied operates more strongly in the strategic perspective of survival, whose main feature is the fact that organizations that work in this perspective seek to ensure their profitability in the present, emphasizing the strengths and addressing the weaknesses points of its current resource base and knowledge.